2022
DOI: 10.7250/bjrbe.2022-17.582
|View full text |Cite
|
Sign up to set email alerts
|

Use of Recycled Asphalt and Waste Materials in Production of High-Performance Asphalt Mixtures

Abstract: The research has been conducted to test the asphalt produced in Latvia using local mineral materials and local recycled modifiers (fiberglass, crumb rubber), as well as the recycled asphalt used in the production of high-modulus asphalt mix, which will meet the local Latvian road construction specifications and will be economically, environmentally and technically more attractive. In the theoretical part, the available sources were studied to establish a theoretical framework, assess possibilities for using re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…Several material factors can affect the thermal behaviour of asphalt mixes, such as the binder type, aggregate type and grading, bitumen content and air voids content (Jung & Vinson, 1994). Izaks et al (2022) showed in their study that the lowtemperature cracking resistance of dense graded high modulus base layer asphalt did not decline when high RA content was added along with glass fibers.…”
Section: Performance Considerations When Incorporating High Ra Conten...mentioning
confidence: 96%
“…Several material factors can affect the thermal behaviour of asphalt mixes, such as the binder type, aggregate type and grading, bitumen content and air voids content (Jung & Vinson, 1994). Izaks et al (2022) showed in their study that the lowtemperature cracking resistance of dense graded high modulus base layer asphalt did not decline when high RA content was added along with glass fibers.…”
Section: Performance Considerations When Incorporating High Ra Conten...mentioning
confidence: 96%